THE RELATIONSHIP OF KNOWLEDGE ON THE PREVENTION OF DIABETES MELLITUS MOTIVATION IN STUDENTS - Achmad Sya'id (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Health students were identified as having bad habits in consuming and life style related to DM type II prevention, which should be a role model and provide examples of how to behave in a healthy life style to prevent illness. Health students, especially nursing, have the ability to keep many information as a memory known as retention. Retention is declaired as any information kept in the brain as a memory and not being forgotten. The purpose of this study was to determine the relationship between knowledge and motivation to prevent diabetes Mellitus. This study used a cross sectional, 97 samples filled out a questionnaire about knowledge and motivation to prevent Diabetes Mellitus. The results of statistical tests using the Chi-Square test showed p value (p-value) = 0.760 > (>= 0.05). This shows that there is no relationship between knowledge and motivation to prevent type II diabetes mellitus. Poor motivation may be caused by the influence of commersial advertising and lifestyle that is less able to support prevention of type II Diabetes Mellitus